A study on the dynamic response of the double pantograph interaction with rigid catenary - M. Simarro; S. Postigo; P. Reyes; R.J. Luque; P.V. Baćić; J.J. Castillo (Engineering Structures, 2025)

How Old Is the Presence of the Canary Pine Forests in the Canary Islands? - C. A. Góis‐Marques; E. Martín‐González; J. M. Postigo‐Mijarra; M. C. Velasco‐Flores; C. Castillo Ruiz; M. Menezes de Sequeira (Journal of Biogeography, 2025)
Aim The Neogene fossil record of Pinus canariensis C.Sm ex DC. suggests a wider past distribution in Europe, but due to extirpation by past climatic events, today this taxon is restricted to the Canary Islands. Remarkably, the putative oldest P. canariensis fossil for the Canary Islands, found in Gran Canaria is 13.3–13.0 Ma. This palaeobiogeographical information has been cited as proof of the deep‐time presence of conifers, the genus Pinus L., P. canariensis and the pine forest ecosystems in the Canary Islands, but also to justify the long‐term evolution of P. canariensis within an active insular volcanic environment. Here we present a re‐evaluation of the oldest Pinus fossil from the Canary Island. Location Gran Canaria, Canary Islands, Spain. Taxon Pinus canariensis C.Sm ex DC. Methods We compiled a citation record for the mentions of the ‘bark fossil’ and conducted a review of the specimen. We compared it with extant P. canariensis and with pyroclasts. Results The analysis of the specimen demonstrates that it lacks morphological or anatomical characters to identify as a bark or even as a plant fossil. The specimen is best interpreted as a lapilli‐sized tube pumice, highly altered by mineral deposition promoted by the percolating hydrothermal water. Main Conclusions The oldest reliable Pinus fossils from the Canary Islands are 3.9–3.1 Ma and ca. 9 to 10 Ma younger than previously claimed. When did Pinus arrive at the Canary Islands is unknown, but this biogeographical question can be approached via focused volcano‐stratigraphical and palaeobotanical research in this Archipelago.

New macrofossil evidence detail the Holocene vegetation of the Iberian Central System - Salvia García-Álvarez; Mar Génova; Ignacio García-Amorena; Carlos Morla; Sergio Rastrero; José M. Postigo-Mijarra (Review of Palaeobotany and Palynology, 2024)

What's on the horizon for community-based conservation? Emerging threats and opportunities - Nafeesa Esmail; Jana M. McPherson; Latoya Abulu; Thora Amend; Ronit Amit; Saloni Bhatia; Dominique Bikaba; Typhenn A. Brichieri-Colombi; Jessica Brown; Victoria Buschman; Michael Fabinyi; Mohammad Farhadinia; et al. (Trends in Ecology & Evolution, 2023)

Floristic changes in the Iberian Peninsula and Balearic Islands (south‐west Europe) during the Cenozoic - José M. Postigo Mijarra; Eduardo Barrón; Fernando Gómez Manzaneque; Carlos Morla (Journal of Biogeography, 2009)
Aim The aim of this work was to identify the main changes in the flora and vegetation of the Iberian Peninsula over the Cenozoic Era, to record the disappearance of taxa associated with these changes and to determine the influence of climate and human activity on these events. Location The Iberian Peninsula and Balearic Islands. Methods A critical review was made of the palaeobotanical literature with the aims of detecting patterns of floristic change and extracting information on the disappearance of different taxa over the Cenozoic. These data are viewed alongside the most recent data for the climate of this period. A critical analysis is made of the role of Palaeotropical and Arctotertiary taxa in the forest communities of the Iberian Peninsula throughout the Cenozoic. Results Although the Eocene–Oligocene transition was a time when many taxa disappeared, the most outstanding events occurred between the end of the Oligocene and throughout the Miocene. Substantial floristic changes took place over this period, including the disappearance of 177 Palaeotropical taxa. This was probably related to acute cooling and aridification; no evidence exists that the Messinian Salinity Crisis had any important effect in the Iberian Peninsula. The last great disappearance of Palaeotropical taxa (36 in total) ended in the Middle–Late Piacenzian; Arctotertiary taxa were most affected during the Pleistocene. The Lower–Middle Pleistocene transition, best represented by marine isotopic stages (MIS) 36–34 and 20–18 and characterized by a change in glacial cyclicity, was the time of the last notable disappearance of taxa. Main conclusions This work provides the first chronogram of extinctions for the Iberian flora, and records the disappearance of 277 taxa during the Cenozoic. A clear relationship was detected between the main climatic events and the latest appearances of the different taxa.

Molecular detection of Ehrlichia ruminantium infection in Amblyomma variegatum ticks in The Gambia - B. Faburay; D. Geysen; S. Munstermann; A. Taoufik; M. Postigo; F. Jongejan (Experimental and Applied Acarology, 2007)